im not sure of the way uve written out the question but im assuming it is as follows:
multiplying throughout by the LCM which is 8, we get:
2(x-2) -4 = 3x +1
distributing the 2, we get:
2x-4 -4 = 3x +1
x = -9
2006-09-05 16:05:56
·
answer #1
·
answered by Anonymous
·
0⤊
0⤋
The easiest way is to multiply both sides by 8, so we can work with even numbers...
so..
8((x-2)/4)-8(1/2)= 8*(3x + 1)/8
2(x - 2) - 4 = 3x + 1
See... now the algebra is a bit simpler...
2x - 4 - 4 = 3x + 1
2x - 8 = 3x + 1
-8 = x + 1
-9 = x
so... x = -9... I think :)... someone else?
2006-09-05 23:07:34
·
answer #2
·
answered by Barry W 1
·
0⤊
0⤋
1. (x-2)/4 - 1/2 = (3x+1)/8
2. 2(x-2) - 4 = 3x + 1 (multiplying by 8 to clear the fractions)
3. 2x - 4 -4 = 3x +1 (clearing factor)
4. -4 -4 -1 = 3x -2x (transposing)
5. -9 = x (solving for x)
2006-09-05 23:13:41
·
answer #3
·
answered by Skyeman 2
·
0⤊
0⤋
((x - 2)/4) - (1/2) = (3x + 1)/8
Multiply everything by 8
2(x - 2) - 4 = 3x + 1
2x - 4 - 4 = 3x + 1
2x - 8 = 3x + 1
-x = 9
x = -9
2006-09-05 23:47:29
·
answer #4
·
answered by Sherman81 6
·
0⤊
0⤋
That's funny that we're all doing your homework for you.
2006-09-05 23:08:12
·
answer #5
·
answered by huh 4
·
0⤊
0⤋